Prevention of shoulder injuries in overhead athletes: a science-based approach - Cools, A. M.; Johansson, F. R.; Borms, D.; Maenhout, A. (Brazilian Journal of Physical Therapy, 2015)
The shoulder is at high risk for injury during overhead sports, in particular in throwing or hitting activities, such as baseball, tennis, handball, and volleyball. In order to create a scientific basis for the prevention of recurrent injuries in overhead athletes, four steps need to be undertaken: (1) risk factors for injury and re-injury need to be defined; (2) established risk factors may be used as return-to-play criteria, with cut-off values based on normative databases; (3) these variables need to be measured using reliable, valid assessment tools and procedures; and (4) preventative training programs need to be designed and implemented into the training program of the athlete in order to prevent re-injury. In general, three risk factors have been defined that may form the basis for recommendations for the prevention of recurrent injury and return to play after injury: glenohumeral internal-rotation deficit (GIRD); rotator cuff strength, in particular the strength of the external rotators; and scapular dyskinesis, in particular scapular position and strength.